Patrimônios em devir: a fruição da informação dos patrimônios arqueológicos juntos aos seus atores no município de Camalaú, PB - Catoira, Thaís (2018)
This piece of research aimed to reflect, from the fruition, on the memories and representations evoked by the people that inhabit the surroundings or fulfill activities related to the archaeological sites present in the municipality of Camalaú, in the Cariri of Paraíba, in order to understand through the presented information as these cultural manifestations are perceived. Thus, the concept of cultural heritage that goes beyond the material and immaterial dichotomy as well as the notion of patrimonial information, concerning the field of Information Science, were taken into account. In this way, through an ethnographic approach, it was possible to promote different conversations about the archaeological sites of Camalaú, perceiving the different levels of the patrimonialization and institutionalization process that pervade the cultural assets, as well as to identify the different representations that people construct from their cultural, memorialistic repertoires and their social relations. The fruition between cultural goods and people, perceived by the researcher, can generate new mechanisms, representations and methodologies for different professionals who work in the organizational processes, preservation and management of the patrimony, creating alternative ways of approaching the contemporary population and the past patrimonial assets.